Notched and Nonnotched Stimuli Are Equally Effective at the Mixing-Point Level in Sound Therapy for Tinnitus Relief - Jin, In-Ki; Choi, Soon-Je; Ku, Minseung (Journal of the American Academy of Audiology, 2021)
Background Broadband noise (nonnotched) and notched noise are common sound sources in sound therapy for tinnitus relief. Studies on sound therapy using nonnotched or notched stimuli have reported large and small tinnitus improvements depending on the participant. However, the more effective sound source remains unclear given the among-study methodology differences.Purpose This study aimed to evaluate the tinnitus relief effects of sound therapy using stimuli with different spectral characteristics.Research Design This was a prospective study involving within-subject (baseline vs. 12-month follow-up) measurements for two groups (notched noise group vs. broadband noise group).Study Sample We enrolled 30 adults with subjective and tonal tinnitus (notched noise group: 16, broadband noise group: 14).Intervention The participants underwent 3-hour daily sound therapy using either notched noise or broadband noise for 12 months. The stimulus level for sound therapy was set to each participant's mixing point.Data Collection and Analysis Tinnitus loudness and the Korean version of the Tinnitus Primary Function Questionnaire score were measured at baseline and at the 12-month follow-up time point.Results Both groups showed a significant improvement in tinnitus loudness and the Korean version of the Tinnitus Primary Function Questionnaire score.Conclusion Notched and nonnotched stimuli are equally effective at the mixing point in sound therapy for tinnitus relief. Individuals with difficulties in tinnitus frequency measurement could easily undergo sound therapy using nonnotched stimuli.
Keywords: tinnitus; sound therapy; broadband noise; notched noise